Modal Analysis and Optimization Method of Flexspline of Harmonic Reducer - Yang Wang; Qianqian Liu; Xiaobiao Mu; Hao Wang (Jixie chuandong)
In response to the design requirements of miniaturization，lightweight and high resonance frequency of the flexspline，the inner diameter，aspect ratio，thickness-diameter ratio and tooth width coefficient of the flexspline are used as research variables. Based on the finite element Ansys，the response surface method parameter optimization analysis is used to explore the influence of the changes of each parameter on the natural frequency of the flexspline. The results show that，in the design process of the flexspline miniaturization，the decrease of the inner diameter and the aspect ratio of the flexspline will increase its natural frequency，and the decrease of the thickness-diameter ratio and the tooth width coefficient will increase its natural frequency，but its natural frequency is greater than the working excitation frequency of the reducer，and resonance will not occur to affect normal operation.